2021
DOI: 10.1007/s00784-021-04093-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of inflammatory mediators in biofilm samples and clinical association in inflammatory bowel disease patients—a preliminary study

Abstract: Objectives Inflammatory bowel disease (IBD) has multiple impacts on soft and hard tissues in the oral cavity. The aim of this study was to analyze the expression of cytokines in biofilm samples from patients suffering from IBD and compare them to healthy patients. It was hypothesized that different cytokine expression levels and clinical associations might be drawn. Material and methods A total of 56 biofilm samples from three different patient cohorts (gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Elevated serum concentrations of IL-10 in active UC and CD-patients as compared with healthy controls have been previously reported 41,42 . Overexpression of IL-10 in subgingival biofilm samples for UC and CD-patients as compared with healthy controls have also been demonstrated 27 . In contrast, other studies have shown similar or lower IL-10 levels in the serum of patients with UC and CD as compared with non-IBD patients 43,44 .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Elevated serum concentrations of IL-10 in active UC and CD-patients as compared with healthy controls have been previously reported 41,42 . Overexpression of IL-10 in subgingival biofilm samples for UC and CD-patients as compared with healthy controls have also been demonstrated 27 . In contrast, other studies have shown similar or lower IL-10 levels in the serum of patients with UC and CD as compared with non-IBD patients 43,44 .…”
Section: Discussionmentioning
confidence: 95%
“…36,37 Prior studies have reported elevated levels of proinflammatory and anti-inflammatory mediators and MMPs, such as IL-4, -10, -17A, -18, -21, IFN-γ, MMP-7, and MMP-8, in the periodontal tissues of patients with IBD. 12,27,38 To the best of our knowledge, the present study was the first to examine the selected inflammatory mediators in both saliva and GCF in UC, CD, and patients with non-IBD according to their periodontal status. In this study, UC group of patients had the highest salivary concentrations of TNF-α as compared with CD and non-IBD groups for both patients with periodontitis and gingivitis.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The clinical, respective laboratory examination was based on the equivalent protocol and established in the laboratory of the Department of Oral and Maxillofacial Surgery to analyze biofilm samples with regard to inflammatory markers [21].…”
Section: Data Extraction and Examinationmentioning
confidence: 99%